Caveolin-1 in Stroke Neuropathology and Neuroprotection: A Novel Molecular Therapeutic Target for Ischemic-Related Injury - Wang, Shanshan; Head, Brian P. (Current Vascular Pharmacology, 2019)
Cardiovascular disease and associated cerebral stroke are a global epidemic attributed to genetic and epigenetic factors, such as diet, life style and an increasingly sedentary existence due to technological advances in both the developing and developed world. There are approximately 5.9 million stroke-related deaths worldwide annually. Current epidemiological data indicate that nearly 16.9 million people worldwide suffer a new or recurrent stroke yearly. In 2014 alone, 2.4% of adults in the United States (US) were estimated to experience stroke, which is the leading cause of adult disability and the fifth leading cause of death in the US There are 2 main types of stroke: Hemorrhagic (HS) and ischemic stroke (IS), with IS occurring more frequently. HS is caused by intra-cerebral hemorrhage mainly due to high blood pressure, while IS is caused by either embolic or thrombotic stroke. Both result in motor impairments, numbness or abnormal sensations, cognitive deficits, and mood disorders (e.g. depression). This review focuses on the 1) pathophysiology of stroke (neuronal cell loss, defective blood brain barrier, microglia activation, and inflammation), 2) the role of the membrane protein caveolin- 1 (Cav-1) in normal brain physiology and stroke-induced changes, and, 3) we briefly discussed the potential therapeutic role of Cav-1 in recovery following stroke.
Keywords: inflammation